Perchance to dream: dream divination in the Bible and the Ancient Near East - Hamori, Esther J.; Stökl, Jonathan (Ancient Near East monographs, 2018)
This book examines the interpretation of dreams, which were thought to contain divine messages in the ancient Near East. For the first time in a single collection, scholars examine how dream divination was used in different ancient cultures. The essays, written by scholars specializing in different regions and bodies of literature, shed light on dream divination in the Bible, the Talmud, and in writings from Canaan, Mesopotamia, and Hittite Anatolia. Contributors include Franziska Ede, Esther J. Hamori, Koowon Kim, Christopher Metcalf, Alice Mouton, Scott B. Noegel, Andrew B. Perrin, Stephen C. Russell, Jonathan Stökl, and Haim Weiss. - from publisher